Converter Circuit "Voltage-Voltage" Investigation for Power Calibrator; Journal of Physics: Conference Series; Vol. 671 : Innovations in Non-Destructive Testing (SibTest 2015) - Fomichev Yu. M. Yury Mikhailovich (2016, 2016)
Title screen